Unsur Intrinsik Drama Dag Dig Dug Karya Putu Wijaya - Ines Astria Oktavia; Sariyanti Sariyanti; Selviana Bella Belinda; Tiara Nurwafa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The drama “Dag Dig Dug” by Putu Wijaya is an interesting literary work to analyze, especially in terms of its elements. This research was conducted to understand the intrinsic elements in the drama Dag Dig Dug by Putu Wijaya. Intrinsic elements are important elements in a literary work. A work cannot be called a literary work if one of the elements is not present in it. This research aims to understand the important elements in the drama, such as theme, plot, character, setting, dialog, and mandate, so that we can understand the meaning contained in it. The problem to be answered in this study is what elements exist in Putu Wijaya's Dag Dig Dug drama and how these elements are interconnected to form a story. The purpose of this research is to explain these elements. The main data source is the play Dag Dig Dug by Putu Wijaya and several journals and other relevant sources. The method used is qualitative with a literature study approach. The author collects and analyzes various literary theories to identify the elements in the script. The results show that the elements in this drama include theme, character, plot, setting, dialog, and mandate. The theme is about life. There are 8 characters in this drama. The plot uses a loose plot. The setting of the story is in the house of a husband and wife. The dialog of the eight characters helps reveal the story. The mandate is about the importance of applying moral and ethical values, especially the value of honesty in life. Overall, the elements in Putu Wijaya's Dag Dig Dug interact with each other to create a work that is not only entertaining, but also thought-provoking for the audience. This research is expected to provide deeper insight into Putu Wijaya's work and the elements that make up a drama in Indonesian literature.